Activity-Based Management sebagai Strategi Efisiensi Biaya dalam Mendukung Daya Saing Usaha Mikro Kecil dan Menengah - Kiky Anggrita; Adhalia Tryani; Jainal Arifin; Marliani Marliani; Mukhtaruddin Mukhtaruddin (GLOBAL SCIENTS PUBLISHER, 2026)
This study analyzes the effectiveness of implementing ABM in enhancing cost efficiency within the Micro, Small, and Medium Enterprises (MSMEs) and Small and Medium Industries (SMIs) sectors.Cost efficiency is a crucial issue because many MSMEs still face limitations in their accounting systems, distortions in overhead cost allocation, and suboptimal mapping of production activities, which affect the accuracy of strategic decision-making. This study uses a qualitative approach through the Systematic Literature Review (SLR) method on scientific articles from 2020 to 2025 that discuss the implementation of ABM in the context of small and medium industries. The results of the synthesis indicate that ABM enhances cost efficiency by identifying and eliminating non-value-added activities, with potential cost savings ranging from 0.52% to 7.5%, depending on the complexity of costs and the organization’s level of readiness. In addition, ABM improves cost information accuracy, improves overhead allocation, and strengthens the basis for strategic decisions. However, there is a gap between theoretical potential and practice, especially in MSMEs with limited systems and technology